Comparative molecular genetics of the German Shepherd dog - Coutts, Natalie June (Division of Chemical Pathology, 2004)
Includes bibliographical references (leaves 105-111). Microsatellite markers were used to measure genetic diversity and population differentiation within and between domestic dog breeds. The German Shepherd Dog was compared with typical outbred mongrel dogs, Dachshunds, Staffordshire Bull Terriers and a cohort of other pedigreed dogs representing 30 recognised breeds. Although archaeological records report that grey wolves (Canis lupus) were domesticated approximately 14 000 years ago, mtDNA analysis suggests that domestic dogs (Canis familiaris) and grey wolves diverged in multiple events over 100 000 years ago. Subsequently, the movement of humans and their dogs resulted in extensive gene ﬂow between dog populations for thousands of years. Breeding practices to obtain distinctive pnenotypic uniformity were recently introduced, resulting in pure-bred dogs becoming essentially closed gene pools. However, further mtDNA analyses have reported unexpectedly high levels of variability, supported by microsatellite loci with heterogeneities of between 36% and 55% being reported for some dog breeds. Microsatellite analyses of 15 polymorphic canine loci are reported. German Shepherd Dogs and outbred mongrel dogs expressed diversity values of 4.0 alleles per locus in the former and 6.4 in the later (corrected for population size by jack-kniﬁng with 1 000 pseudoreplications), with expected heterozygosities of 62% and 83%, respectively. German Shepherd Dogs showed a moderate loss of genetic diversity relative to outbred dogs, but not sufficient to describe the breed as highly inbred. However, in comparison with other pure-bred dogs examined, they expressed the least genetic diversity, with Dachshunds having 5.2, Staffordshire Bull Terriers 4.8 and the composite group of pedigreed dogs 6.0 alleles per locus, with expected heterozygosities of 72%, 67% and 80%, respectively. Signiﬁcant population differentiation (GST = 0.103; RST = 0.058) between German Shepherd Dogs and the outbred dogs illustrates the effect of genetic ...